Schenker studies 2 - Schachter, Carl; Siegel, Hedi (Cambridge Cambridge University Press, 1999)
This is Cambridge University Press' second volume of studies based on the work of Heinrich Schenker (1868-1935), now recognized as this century's most influential figure in the areas of music theory and analysis. The book contains historical studies that derive from Schenker's unpublished papers, and analytical studies of music from the eighteenth to the twentieth centuries. It aims to apply and further develop Schenker's theories and ideas for the benefit of music scholars, performers, and students.